Communication noise of product innovation promotion process - I. Yu. Aleksandrova (Вестник университета)
The communicative noise phenomenon as a destructive element of marketing communication aimed at promoting product innovation has been analyzed. In the process of solving the set tasks the attention has been focused on the study of communicative noise of recipient and addressee of marketing information about an innovative product, since the noises of this type are the most complex and problematic ones due to their latency and weak controllability. Their essence lies in errors/failures of coding-decoding of marketing information in the process of a company’s interaction with potential consumers of its product innovation. As the conducted research result, the following communicative noises of recipient and addressee of marketing information about an innovative product have been identified and analyzed: incorrect positioning of an innovation; semantic dissonance of the brand image and its product innovation; incorrect advertising concept of an innovation; weak or incorrect creative idea of the innovation advertising; incorrect choice of tools for promoting an innovation; differences in the perception of an innovation related to social and demographic characteristics of consumers (gender, sex, age, education, and income), consumers’ belonging to one or another culture (cultural and ethnic or religious affiliation), and individual-psychological characteristics (personality type, individual value system, degree of dependence on the social environment, and the level of resistance to psychological influence).